Adsorptive Removal and Photo-Fenton Degradation of Congo Red Dye from Water Using Modified Gadolinium Orthoferrite - Phan, Thi To Nga; Nguyen, Thi Thu Huyen (JST: Engineering And Technology For Sustainable Development, 2024)
GdFeO3-incorporated zeolite (GFO/Z) was successfully prepared by the impregnation method followed by the calcination process and used for adsorption and photo-Fenton degradation of Congo Red (CR). The as-prepared GFO/Z material was characterized by X-ray Diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM), Brunauer–Emmett–Teller (BET) surface area, and optical absorption spectra (UV-Vis). The large specific surface area and accessible pores supported its high performance towards the adsorption of CR. Besides, due to its low band gap energy, the photo-Fenton catalytic activities of GFO/Z were also investigated for the degradation of CR under visible light irradiation. The use of GFO/Z led to a high removal rate (97.46%) of CR thanks to the synergistic effect between effective dark adsorption and visible-light-driven Fenton degradation, which was greater than those of pure GFO. Scavenger experiments were performed to reveal that the hydroxyl radicals (•OH) were the main active species in the photo-Fenton catalytic process. This work showed a promising application of GFO/Z in the degradation of organic compounds in wastewater.